2021
DOI: 10.32584/jkmk.v4i2.1215
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Karakteristik Perawat dan Safety Attitude di Rumah Sakit Jakarta

Abstract: Sikap keselamatan perawat mempengaruhi tindakan dalam menerapkan implementasi asuhan keperawatan yang berbasis keselamatan pasien. Penelitian ini bertujuan mengetahui hubungan karakteristik perawat dan sikap keselamatan, melalui penelitian cross sectional yang melibatkan 330 perawat di 3 rumah sakit veritkal Jakarta. Instrumen yang digunakan adalah Safety Attitudes Questionnaire dengan tambahan data demografi.  Terdapat hubungan signifikan antara karaktersitik perawat dan sikap  keselamatan perawat. Jenis kela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…In contrast, another previous study showed that age is a factor that affects patient safety attitudes (36). Previous research conducted at the Jakarta Hospital also stated that the age of nurses had a significant relationship with patient safety attitudes (37). The This study also showed no significant relationship between nurses' work experience and nurses' attitudes towards patient safety in the hospital.…”
Section: Resultscontrasting
confidence: 73%
“…In contrast, another previous study showed that age is a factor that affects patient safety attitudes (36). Previous research conducted at the Jakarta Hospital also stated that the age of nurses had a significant relationship with patient safety attitudes (37). The This study also showed no significant relationship between nurses' work experience and nurses' attitudes towards patient safety in the hospital.…”
Section: Resultscontrasting
confidence: 73%
“…Hariyati et al (2018) found that more highly qualified nurses had a smaller chance of making medical errors than less qualified nurses. Suganda et al (2021) reported similar findings, finding that highly qualified nurses were very unlikely to make making medical errors that threatened patient safety. Patient safety knowledge that nurses acquire based on their experience can be expected to make them more careful, leading to fewer mistakes at work.…”
Section: Resultsmentioning
confidence: 58%
“…Research on 185 nurses in a government hospital and 120 nurses in a private hospital in Jambi found that only 45.48% and 56.22%, respectively, of nurses had positive attitudes towards patient safety (Bukhari, 2019). In a research hospital in Jakarta, Indonesia, Suganda et al (2021) reported that 50.91% of nurses had poor safety attitudes. Unsafe patient safety attitudes among nurses can lead to errors and incidents in hospitals (Niknejad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%